Contraceptive use and unintended pregnancies among HIV-infected women in Mumbai - Beena Joshi; Gajanan Velhal; Sanjay Chauhan; Ragini Kulkarni; Shahina Begum; Y S Nandanwar; Michelle Fonseca; Sujata Baweja; Dilip Turbadkar; Anita Ramchandran; Asha Dalal; Jayanti Shastri; et al. (Wolters Kluwer Medknow Publications, 2015)
Background: Access to reproductive health services in Human Immunodeficiency Virus (HIV) programs can greatly enhance program's potential to limit the spread of disease, reduce unintended pregnancies and safeguard the health of infected people. Objectives: To assess (i) knowledge, attitude, and use regarding contraceptives; safe sex and dual protection; (ii) fertility desires and unintended pregnancies post HIV and (iii) symptoms of reproductive tract infection/sexually transmitted infection (RTI/STI) among women infected with HIV. Materials and Methods: A cross-sectional study among 300 currently married HIV-positive women who had not undergone permanent sterilization with no immediate desire for pregnancy. Study site was Integrated Counseling and Testing Centers (ICTC) in tertiary hospitals of Mumbai and women were interviewed using a semistructured questionnaire. Results: In spite of good awareness about modern methods, 42.7 felt that contraceptives other than condoms were harmful to use due to their HIV status. Knowledge on dual protection was limited to condom (75%). Condom use increased from 5.7% pre-HIV to 71.7% post-HIV, with 89.6% reporting regular use. Future fertility desire was expressed by 8.7% women. Induced abortions post-HIV was reported by16.6% women, as pregnancies were unintended. About 69% wished to use dual contraceptive methods for effective protection if it was not harmful to be used by people living with HIV (PLHIV). Conclusion: Data reveals a need to promote modern contraceptive methods along with regular condom use to prevent unintended pregnancies and improve health-seeking behavior for contraception. Health system models that converge or link HIV services with other reproductive health services need to be tested to provide comprehensive reproductive healthcare to infected women in India.